HPAI Epidemic in Egypt: Evaluation, Risk Factors and Dynamic of Spreading - Kaoud, H.A. (International Journal of Poultry Science, 2007)
On 17 February 2006, the Egyptian government confirmed that bird flu had broken out in the nation`s poultry in Egypt. In this work Trials were carried out to determine: The transmission parameter β (i.e., the average rate at which infected flocks infect susceptible flocks) and the infectious periods (T) between various districts. Rh was calculated as the product of the estimates of the transmission parameter and the infectious period. Results revealed that, the infection was spread to 21 governorates, 5 of them with a high density of poultry farms. In all, 826 districts containing commercial flocks became infected during a period of 4 months. Suggested geographic maps for the spread of HPAI virus that had been stroked Egypt 2006 were constructed. The transmission parameters varied in-between the districts in the various governorates. It was ranged from 23 days to 87 days. Governorates of heavy density (number of poultry farms per km2) have less periods for the transmission of the virus from district to another. It was found a negative correlations between the number of the infected farms of the governorate and (T) parameter of transmission (r = -0.415 at P<0.05) and a negative significant one between the number of infected districts and parameter (T) (r =0.51 at P < 0.05). Also there was a significant correlation between the number of infected districts and the activity of the transporting traffic of poultry between the districts of the same governorate and to other governorates (r =0.66 at P < 0.05). Parameter (T), it was ranged from 0.36 day to 27.6 days. Rh between-districts transmission decreased significantly after virus detection, it was still > 1 (R =1.2 for both areas) suggested that the control measures were inadequate to interrupt the chain of infection. The association between the presence of the migratory birds and the occurrence of AI infection, was determined, where the relative risk was 1.17 and the magnitude of this association = 0.12 (attributable risk) i.e. 12 % of infection probably owing to migratory birds.